The seismic reliability analysis of moment resisting frames with bolted end-plate connection. (August 2020) - Radmehr, Mostafa; Homami, Peyman
Abstract: This paper presents an algorithm to determine the reliability index of moment-resisting steel frames with bolted end-plate connections, by considering the effect of the uncertainties of capacity and seismic demand. To reflect the probabilistic response of structures, the horizontal and vertical distance of the bolt from edge of end-plate, the pretension force and the ultimate strength of the bolts, yield strength and the elastic modulus of plates for beam and column, which are the main parameters of construction errors in bolted end-plate connection, considered as a random variables for the moment-rotation behavior of connections. All the components of the connections have been regarded as random parameters. Then, the probabilistic moment-rotation curve of connections was determined by means of the Latin Hypercube sampling method. Afterward, by conducting a nonlinear dynamic analysis in the 2-dimensional 5, 10, and 15 stories frames and considering the idealized random behavior of the connections as well as the random effect of different records of the earthquake, the results obtained with the aid of Monte Carlo sampling technique. Finally, the appropriate probability density function (PDF) fitted to the results, which this figure for reliability index and probability of failure for the limit state function is 1.62 and 0.052 respectively and also the mean value state is 1.85 and 0.033. This procedure has been named as the Simplified Response Surface Method (SRSM). Results show the structural reliability index is acceptable at the performance level of Life Safety, yet it exceeded this level only by a small amount. Highlights: The Simplified Response Surface Method (SRSM) is introduced for assessment the structural reliability. Latin Hypercube sampling method is utilized to estimate the bounded limit of the behavior of the beam to column connection. Monte Carlo sampling technique is utilized to calculate the reliability index of the steel frames. Sensitivity analysis is utilized to determine the most important uncertainties in the beam to column connection.